Alternate business models for Colombian msmes based on corporate social responsibility, fair trade, inclusive businesses and shared value (2016)
Purpose: The objective of this article is to propose a strategic alternative to msmes and new Colombian entrepreneurs, based on corporate social responsibility (csr), trade fair, inclusive business and shared value, as an option for new forms of production and development. Description: Each of the topics is discussed independently through a brief overview in order to make the reader aware of the new practices of doing business. Point of view: It is considered relevant and timely to establish an academic reflection that leads to visualize the action fields of csr in the Colombian case. Thus, research is needed to, first, provide clarity about the theoretical roots of csr and, at the same time, build the theoretical framework in which it is possible to identify the concepts it relates to. Conclusions: The commitment of new or renewed entrepreneurs should be thinking about the progress in their employees’ quality of life and the good living of their families, reverse logistics and supply chain sustainability, among others.